2018
DOI: 10.5005/jp-journals-10024-2262
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life-related “Patient-reported Outcome Measures” in Oral Submucous Fibrosis Patients

Abstract: Aim:The aim of this study was to explore the patients' perspectives about the impact of oral submucous fibrosis (OSF) on life quality. Materials and methods:Thirty clinically diagnosed OSF patients with a wide degree of disease severity and diverse range of sociodemographic profile were included in this study. Fourteen participants were interviewed and four focus group discussions were conducted in nonclinical settings. The audio recordings were anonymized, transcribed, and translated in English from Marathi l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…On statistical analysis, a significant difference in the QoL was observed between the diseased and the control groups. The study reported that patients with OSMF had a negative impact on their social and personal relationships [13]. The key feature of their study was that the researchers measured QoL outcomes at different intervals after diagnosis of OSMF when the patients were undergoing clinical trials with different medications.…”
Section: Discussionmentioning
confidence: 99%
“…On statistical analysis, a significant difference in the QoL was observed between the diseased and the control groups. The study reported that patients with OSMF had a negative impact on their social and personal relationships [13]. The key feature of their study was that the researchers measured QoL outcomes at different intervals after diagnosis of OSMF when the patients were undergoing clinical trials with different medications.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterised by inflammation followed by fibrosis of the submucosa, which causes stiffness, a limited range of mouth opening and atrophy of the oral epithelium. In advanced stages of the disease, OSF has considerable negative effects on quality of life, including functional limits and psycho‐social impairment (Gondivkar, Bhowate, Gadbail, Gondivkar, et al, 2018; Gondivkar, Bhowate, Gadbail, Sarode, et al, 2018; Raja et al, 2013). People from South and South East Asian nations or Southern Asian immigrants to other regions of the world are more likely to suffer from OSF (Tilakaratne et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This results in to increasing stiffeness and marked rigidity of the tissues leading to reduced mouth opening, significantly compromising the patient’s QoL. It is evident that OSF have detrimental effects on OHRQoL and the worsening of QoL has been associated with advanced stages of OSF[ 15 ].…”
Section: Introductionmentioning
confidence: 99%